2019
DOI: 10.1021/acsami.9b02911
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Nanobuds: A New Second-Generation Phosgene Sensor with Ultralow Detection Limit in Aqueous Solution

Abstract: Selective and sensitive detection of highly toxic chemicals by a suitable, fast, inexpensive, and trustworthy method is vital due to its serious health threats to humankind and breach of public security caused by unexpected terrorist attacks and industrial accidents. Phosgene or carbonyl dichloride is widely employed in many chemical industries and pharmaceuticals, and in pesticide production, which is extremely toxic by severe (short-term) inhalation exposure. Because of the non-existence of a phosgene sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…SI11 †). 25 From the abovementioned electron microscopy results, we largely concluded that DAN-GQD in nanobud morphology can be propitious for the electrochemical determination of Ce 3+ ions without changing its morphology even in acidic conditions.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…SI11 †). 25 From the abovementioned electron microscopy results, we largely concluded that DAN-GQD in nanobud morphology can be propitious for the electrochemical determination of Ce 3+ ions without changing its morphology even in acidic conditions.…”
Section: Resultsmentioning
confidence: 83%
“…11a and b). Aer the electrochemical studies, the X-ray diffraction (XRD) prole of the GNB-modied-CF electrode was centered at 24.95 (002), which indicates that there was no change in the graphitic structure of GNB aer the adsorption of Ce 3+ ion onto the electrode surface 25 (Fig. 11c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The wide-ranging properties of CQDs and GQDs allow their exploration in almost all the fields including biological sciences, 3,4 electronics, 5 energy devices, 6 sensors, 7 agricultural, 8 cosmetics, 9 pharmaceuticals, 10 and medical devices. 11 Both the QDs possess characteristic properties such as low toxicity, great solubility in a variety of solvents, good optoelectronic behavior, strong inertness toward chemicals, high surface area, and surface edges for functionalization.…”
Section: Introductionmentioning
confidence: 99%